2017
DOI: 10.1021/acsinfecdis.6b00179
|View full text |Cite
|
Sign up to set email alerts
|

A Screen for Protein–Protein Interactions in Live Mycobacteria Reveals a Functional Link between the Virulence-Associated Lipid Transporter LprG and the Mycolyltransferase Antigen 85A

Abstract: Outer membrane lipids in pathogenic mycobacteria are important for virulence and survival. While biosynthesis of these lipids has been extensively studied, mechanisms responsible for their assembly in the outer membrane are not understood. In the study of Gram-negative outer membrane assembly, protein-protein interactions define transport mechanisms, but analogous interactions have not been explored in mycobacteria. Here we identified interactions with the lipid transport protein LprG. Using site-specific phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…Compounds that inhibit proper mycolyltransferase localization could be efficacious, as deletion of a single mycolyltransferase can profoundly affect cell viability (44). Moreover, mycolyltransferases can engage in protein-protein interactions, as Msmeg_6398 has been found to interact with LprG, a lipid transport protein; this interaction could confine the enzyme within the cell envelope (45). Alternatively, since mycolyltransferases are secreted, their mechanism of export could influence their localization.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds that inhibit proper mycolyltransferase localization could be efficacious, as deletion of a single mycolyltransferase can profoundly affect cell viability (44). Moreover, mycolyltransferases can engage in protein-protein interactions, as Msmeg_6398 has been found to interact with LprG, a lipid transport protein; this interaction could confine the enzyme within the cell envelope (45). Alternatively, since mycolyltransferases are secreted, their mechanism of export could influence their localization.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, O‐AlkTMM‐C7 allowed the first direct visualization of AGM biosynthesis during cell growth and division in M. smegmatis ( Msmeg ) . O‐AlkTMM‐C7 was also used to assist in the functional characterization of a protein involved in mycomembrane construction, namely the mycobacterial lipid transporter, LprG . In another example, O‐AlkTMM‐C7 was shown to label mycomembrane‐resident O‐mycoloylated proteins in Cglut (via the pathway shown in Figure A), providing a chemical biology approach to the discovery and characterization of this distinctive class of proteins .…”
Section: Introductionmentioning
confidence: 99%
“…This pointed at a metabolic defect in the deletion mutant being responsible for decreased virulence in mice and further lent support to the operon’s role in the transport of triacylated lipids. In a very recent study, LprG was found to interact with various periplasmic proteins, including mycolyltransferase Ag85A, which catalyzes the formation of TDM in the cell wall (Touchette et al , ).…”
Section: Introductionmentioning
confidence: 99%